PARAMETERS IN FORMULATIONS AND SOLUTIONS OF INTRODUCTORY PROBABILITY PROBLEMS - Sondore, Anita; Daugulis, Pēteris (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
Mathematical problems with parameters offer a higher semiotic complexity level of mathematical activities. The topicality of the research is determined by the fact that there are no studies on types of parameters in formulations and solutions of probability problems. The study aims are to analyse the current literature and propose an approach to classify parameters depending on their nature. Methodology - qualitative content analysis of probability problems from published textbooks and research papers. The main result - a parameter classification and interpretation scheme for introductory probability problems. The proposed parameter classification can help differentiate and individualise the study of probability theory and statistics.